ANALISIS NILAI TAMBAH IKAN TUNA MARLIN MENJADI ABON IKAN TUNA PADA CV. RAJA BAWANG DI KOTA PALU - Rafel, Made; Asih, Dewi Nur; Khatima, Husnul (Fakultas Pertanian, Universitas Tadulako, 2024)
This research was conducted at CV. Raja Bawang located at Jl. Abdurahman Saleh No. 33, South Birobuli Village, South Palu Subdistrict, Palu City during February and March 2022. It specifically chosen for its relevance in the industry. Respondents included the leadership and employees of CV. Raja Bawang. The Hayami Method was used to analyze the value-added. Findings indicated that the processing of marlin tuna into tuna floss resulted in an added value of IDR 46,215/kg, yielding a profit of IDR 44,438/kg, or 96.15%. This suggests that the production of tuna floss significantly enhances the economic growth of CV. Raja Bawang. The value-added ratio was 40.01%, equivalent to IDR 18,490, influenced by output value, raw material costs, and other inputs. In February 2022, CV. Raja Bawang processed 360 kg of tuna meat to produce 120 kg of tuna floss, generating an income of IDR 16,088,064/month. These findings demonstrate the significant economic benefits of value-added processing in the tuna industry.